In Search of the Muslim Intellectual - Ahmad, Saiyad Fareed Ahmad Saiyad Nizamuddin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
In Search of the Muslim Intellectual